HIGH INVOLVEMENT MANAGEMENT AND ITS ROLE IN PROMOTING FEELINGS OF ORGANIZATIONAL BELONGING AN ANALYTICAL STUDY OF THE OPINIONS OF A NUMBER OF EMPLOYEES AT THE OIL TRAINING INSTITUTE – BAIJI - Mohammed Ali Abdullah (Scholar Express Journals, 2023)
The research aims to test the relationship and effect between the practices of high containment management and the feelings of organizational affiliation, and in order to achieve this, the dimensions of the practices of high containment management were adopted, represented by (functional integration, training, motivation, information sharing, work teams), and the dimensions of organizational affiliation were adopted, represented by (emotional affiliation, normative affiliation, and continuous affiliation). As the Petroleum Training Institute was chosen as a field for the study, and the questionnaire was used as the main tool for collecting data and information that was prepared for this purpose, The research community was represented by a number of workers, amounting to 38 individuals, to represent the research sample, as 35 questionnaires that were valid for analysis were retrieved, and the researcher used a number of statistical methods to analyze the practical side of the research, such as the arithmetic mean, standard deviation, Pearson's correlation coefficient, and the simple regression coefficient. The research concluded that the management of high containment significantly affects the promotion of feelings of organizational belonging
Keywords: high containment management; organizational affiliation